Editorial analysis of Belarusian-language content of the corporate website (on the example of the websites of the companies «Alivaria» and «Krinitsa») - Zhauniarovich, Piotr P. (Journal of the Belarusian State University. Journalism, 2022)
The main approaches to editorial analysis of a corporate website are considered. At the macro level, ease of navigation, content of individual headings, visualisation, information update and other characteristics are estimated, at the micro level, the quality of the texts posted on the website is determined. It is emphasised that they have numerous deficiencies, which are classified according to all language parameters: orthographic, punctuation, lexical, grammatical and technical. There is an influence of bilingualism on Belarusian-language materials, uncreative translation, and a lack of editing before posting verbal content on the site.